Religious Moderation Perspectives and Pratices in Muslim Youths With International Exposure - Adnan, Muhammad; Husna, Nailul; Fauziah, Ni’matul (JURNAL ILMU SOSIAL, 2024)
Travel across border give opportunity to people to immerse in a diverse groups and  societies. It is hoped to enrich life experiences that lays the groundwork for the creation of  more harmonious and tolerant societies. Religious moderation, especially in Indonesian context, require tolerance, anti-violence, the sense of nationality and local culture acceptance from its citizen to maintain the harmonious, moreover, the unity of Indonesia as a country.  Unfortunately, some Muslim youths were found to have low tolerance toward different religion groups. This study aims to assess if Muslim youths with international exposure have good moderation perspectives and practices in religion, including tolerance. This study is a quantitative descriptive with the help of survey tool to collect data from Muslim youths with international experiences. The analysis was carried out using univariate analysis. The results depict that more than 90% of the 155 respondents have good perspectives and practices toward religious moderation. Only practice of tolerance has slightly lower percentage which is 89%. More international programs for Muslim youths are encouraged to help them increase the level of tolerance toward differences